Strategy for Increasing PAD from Rural and Urban Land and Building Taxes in Ciamis Regency - Soleh Suryadi; Wachyu Hidayat; Eddy Jusuf Sp (Pasundan Social Science Development, 2022)
The main problem of this research is the delegation of PBB–P2 as an effort to increase Local Own-Source Revenue (PAD) is still far from expectations. This research aims to analyze the effectiveness of policy implementation strategies to increase Local Own-Source Revenue (PAD) from the Rural and Urban Land and Building Tax (PBB-P2) in Ciamis Regency. Specifically, this research uses Fred David's theory, where he frames the strategy formulation in three stages, namely, Input Stage, Matching Stage and Decision Stage. The method used in this research is a descriptive research method with a qualitative case study approach. Policy implementation strategy that effectively for the delegating Rural and Urban Land and Building Tax (PBB-P2) into local tax to increase local own-source revenue in Ciamis Regency is a strategy in Quadrant I of the Grand Strategy Matrix which has a superior strategic position , and recommended choosing alternative strategies, namely concentric diversification strategies.